?RELATIVE YIELDS OF CROPS AND CROP LOSSES OUE To WEED COMPETITION IN BANGLADESH (Biological Sciences - PJSIR, 1998)
An estimate of crop losses due to weed competition has been done on the basis of experimental data available in the country. The relative yields of 27 crop species are calculated and the ranking of competitive power of the crop specieshasbeenestablished.Onaverage37.33%ofcropproduceisdamagedifweedsarenotcontrolledinBangladesh. Crops valued at approximately Taka59665.70 million might be lost annuallydue to unrestricted growth of weeds in the country.The pest may cause a loss of 9.66 million tons of food valued atTaka56711.12million ($ 1383million) every year if they are not controlled in the crop fields. Production losses may also occur due to weeds as 33.16% in food crops, 41.26% in cereals, 31.88% pulses, 40.82% in oilseeds, 34.23% in fibre crops and 40.28% in rice crops in the country.However, anaverage of 13.1%of crop produceis actually lostin thefarmers field even after adopting traditional weed controls in Bangladesh. On thisbasis, crops valued atTaka20,938.13 million is lost every year due to weeds. More than 2.5 million tons of food grain (cereals, pulses and oilseeds) valued atTaka 17232.80million is lost per annum. Of the crop species investigated, tea and khesari are the most competitive crops followed by sugar- cane and lentil. Onion is the least competitive crop against weeds.